A 2.4‐GHz dual polarized suspended square plate rectenna with inserted annular rectangular ring slot. Issue 2 (27th October 2015) - Phongcharoenpanich, Chuwong; Boonying, Komkris
ABSTRACT: This research has proposed a dual polarized suspended square plate rectenna for RF‐to‐DC conversion at the 2.40–2.50 GHz frequency band. The proposed dual polarized antenna yields improved isolation with an annular rectangular ring slot etched in the square radiating plate. The proposed antenna could achieve >40.00 dB isolation and >8.00 dBi gain with unidirectional radiation. The proposed SMS7630‐based rectifying circuits were measured and could realize the maximum conversion efficiency of 25.98% (1.57 V) with a 3.00 kΩ resistor and 2.00 mW input RF power of a signal generator. On integration, the experimental vertical polarization rectenna was capable of achieving the maximum conversion efficiency of 21.86% (14.20 mV) at the 0.5 m distance and 0.00015.00 mW/cm 2 input power density. The proposed dual polarized rectenna can receive the input RF power density of arbitrary polarization with obtained average conversion efficiency of 14.97% (10.50 mV) at the 0.5 m distance of wireless local area network (WLAN) system. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:164–173, 2016.